Reflective Perspectives of Host and Guest Participants of an International Professional Development Experience - Melanie J Miller Foster; Joseph Y Cho; Laura L Rice; Brad Kinsinger; Daniel Foster; Nur Husna Abd Wahid (Journal of International Agricultural and Extension Education, 2023)
Global competence is a skill set that has become a necessity in every discipline in the agricultural sciences. With an increasingly diverse student population in our school systems coupled with an increasingly complex global agrisystem, now more than ever we need globally competent educators and learners to develop a globally competent workforce and society. A common intervention in cultivating global competency is the study abroad immersive experience for the traveling participants, but little is known about the global competency gains in hosting individuals. The immersive study abroad experience provided the opportunity for school-based agricultural educators (both candidates and practicing educators) to engage in a four-week experience with their Malaysian counterparts exploring the interconnected nature of culture, agriculture, and education. Throughout the experience the participants engaged in daily structured reflection sessions using the TIPS method. Journal entries were coded and analyzed for both Malaysia and United States participants. Participants from both countries respectively became more globally competent educators and learners.
Keywords: Immersive study abroad experinece; guest participants; host participants